Novel borosilicate bioactive scaffolds with persistent luminescence - Paloma Roldán Del Cerro; Henriikka Teittinen; Isabella Norrbo; Mika Lastusaari; Jonathan Massera; Laeticia Petit (Walter de Gruyter GmbH, 2022)
Persistent luminescent amorphous borosilicate scaffolds were successfully prepared, for the first time, with a porosity of >70% using the burn-off technique. The persistent luminescence was obtained by adding the SrAl2O4:Eu2+,Dy3+ microparticles: i) in the glass melt or ii) in the glass crushed into powder prior to the sintering. The scaffolds prepared by adding the microparticles in the glass melt exhibits lower persistent luminescence and a slower reaction rate in simulated body fluid than the scaffolds prepared by adding the microparticles in the glass powder due to the release of strontium from the microparticles into the glass during the glass melting.